Observation of Calculated Lapse Rate for Sharia Life Insurance Data : A Study Case - Andaria, Rini; Sumarti, Novriana; Puspita, Dila (Jambura Journal of Mathematics, 2025)
Modeling a lapse rate is an important subject for life insurance companies because a lapse rate can impact the premium pricing, the reserves, and profitability. In this paper, we calculate the lapse rate and implement a similar approach proposed by the Life Insurance Marketing and Research Association (LIMRA) and the Society of Actuaries (SOA). We analyze lapse rate data from one Sharia insurance company in Indonesia, covering an eight-year period with a total of more than one hundred thousand policyholders. Sharia insurance is aimed at managing contributions based on Sharia principles for mutual assistance and protection by providing compensation to participants/policyholders for losses due to an uncertain event or by providing payments based on the death or the survival of participants. We observe the lapse rates by the face amount group, by genders, and by premium payment frequencies. We found three conclusions, which are mostly that the lower the face amount group, the higher the lapse rate; the lapse rate is not significantly different by gender; and the lapse rate for quarterly payment frequency is higher than for other frequencies.